Cassette en geluidsband van redes van Goudkuil en Hulst, muziek van "Zjok", opgenomen in Carré - Goudkuil, Henk.
Cassette en geluidsband van redes van Goudkuil en Hulst, muziek van "Zjok", opgenomen in Carré.